Spatial and temporal distribution of fish egg communities in the adjacent waters of Daya Bay nuclear power plant and their relationship with environmental factors - Zhen Tan; Zhen Tan; Fengxia Wu; Yiyong Rao; Chuanhao Pan; Gang Hou; Honghui Huang (Frontiers in Marine Science, 2023)
The thermal discharge of Daya Bay Nuclear Power Plant has a certain impact on the ecological environment of the adjacent waters. In order to understand and evaluate changes in the fish egg community structure in the adjacent waters of Daya Bay Nuclear Power Plant and their relationship with environmental factors, four surveys were conducted to investigate fish eggs in January (winter), March (spring), August (summer) and November (autumn) of 2020. A total of 100,985 fish eggs were collected and 17 taxa were identified, belonging to five orders, 14 families and 17 genera. Among them, Perciformes and Clupeiformes were the main contributing taxa to fish egg species and abundance in the waters adjacent to Daya Bay Nuclear Power Plant. The number of fish egg species ranged from high to low was summer, spring, autumn and winter; the average abundance ranged from high to low was spring, summer, winter and autumn. The results showed that except in winter, the average abundance of fish eggs was greater in northeast area than in southwest area. The Shannon-Weiner species diversity index (H’), Pielou evenness index (J’) and Margalef richness index (d) were significantly different between seasons, but none were significantly different between areas. The results of NMDS analysis showed that there were significant differences in fish egg communities between seasons. Surface seawater temperature the average abundance of fish eggs was positively correlated in the results of all four seasons. Although the entrainment effect of nuclear power plant water intake and thermal pollution of partial waters owing to thermal discharge can cause some loss of fish eggs, fish resources can still be effectively maintained.